Growth Hormone Treatment Increases Plasma Irisin Concentration in Patients with Turner Syndrome - Wikiera, B.; Zawadzka, K.; Łaczmański, Ł.; Słoka, N.; Bolanowski, M.; Basiak, A.; Noczyńska, A.; Daroszewski, J. (Hormone and Metabolic Research, 2017)
Irisin (Ir) deficiency may be a contributing factor in metabolic disease. This study aimed to investigate the effect of supraphysiological doses of recombinant human growth hormone (rhGH) on Ir plasma concentration in relation to metabolic disorders, including obesity and other components of metabolic syndrome. We studied 36 girls with Turner syndrome (mean age 8.2 years) treated with rhGH (0.05 mg/kg/day). Anthropometric data and fasting blood levels [e. g., Ir, insulin, glucose, glycated hemoglobin (HbA1c), IGF-1, IGFBP-3, cholesterol, insulin resistance (HOMA-IR), and β-cell function (HOMA-β)] were analyzed prior to and following rhGH therapy [mean (SD) follow-up of 1.47 (0.89) years]. Insulin sensitivity (Matsuda index) was calculated before and after the glucose load. Following rhGH therapy, an increase in IGF-1 [mean (SD) of 119.40 (62.47) ng/ml to 439.08 (209.91) ng/ml, p=0.000], Ir [2.10 (1.03) μg/ml to 2.48 (0.78) μg/ml, p=0.036], HOMA-IR [median (IQR) of 0.64 (0.45–1.30) to 0.92 (0.67–2.36), p=0.0206], and HOMA-β values [45.00 (27.69–72.00) to 81.53 (51.43–132.00), p=0.0447] were observed. Multiple regression analysis yielded no associations between Ir and metabolic and hormonal parameters before rhGH treatment; however, on rhGH, the model (R2=0.56, adjusted R2=0.45) showed positive associations between Ir and IGF-1 standard deviation score and HbA1c, and negative associations between Ir and fasting blood glucose, HDL-cholesterol, and triglycerides. Despite manifestation of insulin resistance, rhGH application had a positive effect on Ir regulation, and restored physiological conditions of lipid and glucose metabolism.
Keywords: irisin; growth hormone; insulin resistance; metabolic syndrome; HOMA-IR; beta-cell function